The Effect Of Stocking Density and Kind of Feed On Growth and Survival Rate Of North African CatfishLarvae (Clarias gariepinus) - Yollan Sri Hidayah; Sukendi Sukendi; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe aim of this research was to determine the effect of stocking density and kind of food on growth and survival rate of north african catfishlarvae reared with a water recirculation system. This research was conducted from March-April 2019 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. The Method used was a Factorial Completely RandomizedDesign with two factors.The first was stocking density with three levels, namely 10 larvae/L (T10), 20 larvae/L (T20) and 30 larvae/L (T30). While the second factor waskind of feed with two levels namely Tubifex worm and Pasta feed. The larvae were reared in 10 L-glass aquarium with a water recirculating system for 40 days. The result showed that stocking density and kind of feedgave asignificant effect in absolute weight, absolute length, specific growth rate and survival rateof north african catfishlarvae reared in 40 day. The larvae stocked at density of 10 larvae/L and fed on Tubifex worm were significanthythe highest in absolute weight (2,40 gr), absolute length (7,76 cm), spesific growth rate (14,93 %/day) and survival rate (96,00 %). The water quality parameters during research were rangedtemperature26,2-26,8°C, pH 5,2-6,1and dissolved oxygen 3,5-5,2 mg/l. Keywords : Stocking denstity, Kind of feed,North african catfishlarvae